Twin Peaks - Fabrice Defever; Alejandro Ria\~no (Center for Economic Studies and ifo Institute (CESifo), 2017)
Received wisdom suggests that most exporters sell the majority of their output domestically. In this paper, however, we show that the distribution of export intensity not only varies substantially across countries, but in a large number of cases is also bimodal, displaying what we refer to as twin peaks. We reconcile this new stylized fact with an otherwise standard, two-country model of trade in which firms are heterogeneous in terms of the demand they face in each market. We show that when firm-destination-specific revenue shifters are distributed lognormal, gamma, or Fréchet with sufficiently high dispersion, the distribution of export intensity has two modes in the boundaries of the support and their height is determined by a country's size relative to the rest of the world. We estimate the deep parameters characterizing the distribution of export intensity. Our results show that when the conditions for the existence of twin peaks are met, differences in relative market size can explain most of the observed variation in the distribution of export intensity across the world.
Keywords: F12; F14; C12; O50; 330; exports; export intensity distribution; bimodality; firm heterogeneity